THE INFLUENCE OF MOTIVATION AND OCCUPATIONAL HEALTH SAFETY TO THE TURNOVER INTENTION ON CV CAHAYA SHINTA - Yosua Sendefri Pajan; Joy Elly Tulung; Merinda H. Ch. Pandowo (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2023)
Employee Turnover Intention is one important aspect that is needed to be considered and fully minimized in every business’s continuity. Thus, Motivation and Occupational Health Safety are two factors that are important in the understanding of the changing from Employee Turnover Intention. This study aims to figure out the influence of Motivation and Occupational Health Safety to Employee Turnover Intention at CV Cahaya Shinta. Overall population in this research is all employees of CV Cahaya Shinta’s and the chosen sample is 52 respondents. Data analysis uses multiple linear regressions analysis method. This research result proves that Motivation and Occupational Health Safety have positive and significant influence Employee Turnover Intention at CV Cahaya Shinta. Its’ management is obligated to reserve and helping hand Motivation and Occupational Health Safety assessment in this business unit in the proper and contributive matter and deliberate other factors that influence the Employee Turnover Intention at CV Cahaya Shinta. Keywords: motivation, occupational health safety, employee turnover intention